The Effects of Electrification on Employment in Rural Peru - Rosamaría Dasso; Fernando Fernandez (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2013)
We examine the effects of a rural electrification program on employment in Peru. Exploiting the roll-out of the program across districts over time, we adopt differences-in-differences and fixedeffects strategies to estimate the impact of the program on labor market outcomes. The results from our preferred specification suggest that, among males, providing electrification increases hours of work and diminishes the likelihood of having a second occupation. Among females, the treatment rises earnings and these gains seem to be driven by a shift towards non-agricultural jobs. Then, we construct a measure of treatment intensity and show that each additional electrification project increases the magnitude of the estimated impacts (in absolute terms).
Keywords: J22; O13; 330; Electrification; employment; Peru